Integrated Optical Deformation Measurement with TIR Prism Rods - Alexander Wolf (Sensors, 2023)
In this paper, a novel optical measurement principle for deformation, especially torsion, is presented. A laser beam is guided via total internal reflection (TIR) in a prism rod. Every single reflection causes an increasing change in the beam path, which can be measured by its effect on the outcoupling position of the laser. With a diameter of the prism rod of <semantics>10 mm</semantics> and a length of <semantics>120 mm</semantics>, the system achieves torsion sensitivities between <semantics>350 µm/°</semantics> and more than <semantics>7000 µm/°</semantics>, depending on the actual torsion angle <semantics>φ</semantics>. A decency level of sensitivity is defined for comparison, which is exceeded by a factor of <semantics>~55</semantics> at <semantics>φ=0</semantics>. The presented principle of TIR prism rods can be adapted to measure different load cases. Using two laser beams, bending and torsion can be distinguished and combined load cases analyzed. The resulting system can be integrated into machine elements, such as screws, to perform condition monitoring on mechanically loaded components.